Recent Developments and Future Prospects of Manufacturing of Broad Gauge Railway Sleepers Using Waste Materials in India. Issue 1 (November 2020) - Kumar Bagal, Dilip; Kumar Singh, Sangam; Naik, Bibekananda; Barua, Abhishek; Jeet, Siddharth; Parida, Biswajit; Kumar Pattanaik, Ajit
Abstract: Railways form the backbone of all economies, transporting goods, and passengers alike. Sleepers play a pivotal role in track performance and safety in rail transport. Composite sleeper is becoming a suitable alternative for replacing the existing concrete, steel and particularly timber sleeper in both mainline and heavy haul rail network. Composite sleeper technologies are already available but they have gained limited acceptance by the railway industry. A number of composite railway sleeper technologies have been developed but their applications in rail tracks are still limited. This paper discusses in brief about the materials that have been used in making sleepers in the early stages of railways and rigorously reviews the recent developments on composite sleepers and identifies the critical barriers to their widespread acceptance and applications. It has been shown that majority of the sleepers do not last till their expected design life resulting in massive replacement and repair cost. Currently the composite sleeper technologies that are available ranges from sleepers made with recycle materials starting from plastic, rubber, construction waste etc. While these recycled material based sleepers are low cost, the major challenges of using this type of sleepers are their limited strength, stiffness and dynamic properties which in most cases, are incompatible with those of traditional concrete, steel or timber sleeper. This paper rigorously reviews the recent developments on composite sleepers and identifies the critical barriers to their widespread acceptance and applications.